(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article elucidates the issue of early detection of perinatal pathologies in preterm infants. Preterm infants belong to a high-risk group, among which neurological, cognitive, and physical developmental delays are frequently observed. Early identification of perinatal pathologies enables the timely application of early medical interventions aimed at restoring the child’s health. In the study, assessment methods based on neurosonography, electroencephalography (EEG), and biomarkers were analyzed. The results obtained are of significant importance in evaluating the infants’ future developmental prospects and in selecting appropriate early rehabilitation measures.